1978
DOI: 10.1080/0097840x.1978.9934992
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Activity of the Sympathetic Nervous System in Essential Hypertension

Abstract: Plasma catecholamine and norepinephrine concentrations have been measured in carefully characterized ambulatory patients with essential hypertension under basal conditions and following experimental procedures known to enhance sympathetic activity. The studies have demonstrated increased levels of plasma catecholamines in patients with mild hypertension as compared with matched controls following 70 degree upright tilt or cold pressor testing. Considerable heterogeneity was apparent in the population of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In the present study, the patients received fentanyl 2 µg ·kg Ϫ1 in addition to suitable propofol. It has been reported that patients with essential hypertension have increased activity of the sympathetic nervous system [1][2][3] and show an exaggerated hemodynamic response to the induction of anesthesia compared with normotensive patients [14]. Low et al [14] reported that there was a marked increase in NE concentration after laryngoscopy in hypertensive patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, the patients received fentanyl 2 µg ·kg Ϫ1 in addition to suitable propofol. It has been reported that patients with essential hypertension have increased activity of the sympathetic nervous system [1][2][3] and show an exaggerated hemodynamic response to the induction of anesthesia compared with normotensive patients [14]. Low et al [14] reported that there was a marked increase in NE concentration after laryngoscopy in hypertensive patients.…”
Section: Discussionmentioning
confidence: 98%
“…These hemodynamic changes are caused by increased activity of the sympathetic nervous system [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This rather surprising finding may be explained by the inclusion in positive studies of a greater proportion of high-renin hypertensives. 9 ' 27> M ' 73 Alternatively, positive studies may have included hypertensives still under the influence of diuretic therapy, since volume depletion should -at least temporarily -increase both renin activity and NE. The latter explanation is somewhat unlikely, since some studies in untreated hypertensives have reported significant renin-NE relationships.…”
Section: Sodium Balance and Reninmentioning
confidence: 99%
“…However, since resting plasma norepinephrine concentration is determined by both the rate of spillover of norepineph rine from synaptic cleft and the rate of removal of nor epinephrine from plasma [22], the value of resting plasma catecholamine levels as an index of sympathetic activity has been seriously questioned [23]. In contrast, the acute response of circulating norepinephrine to spe cific stimuli was found to be more useful as an indicator of sympathetic responses; this applies in particular to rapid changes in plasma norepinephrine, blood pressure and heart rate in response to head-up tilt [24][25][26], There was a significant elevation of plasma norepinephrine during head-up tilt (from 21 to 176%) observed in our patients, suggesting both intact efferent sympathetic pathways and adequate sensing of the stimulus.…”
Section: Sympathetic Responses In Patients On Chronic Hdmentioning
confidence: 99%